Application of Web 3.0 Tools for the Development of Investigative Skills in Middle School Students - Suárez-Triana, Yolman Mauricio; Rincón-Duran, Ricardo; Niño-Vega, Jorge Armando (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The objective of this research was to propose a pedagogical strategy based on web 3.0 tools, to develop the competence of interpreting and solving research project problems in middle school students. The work had a qualitative approach with an exploratory scope. The study population corresponded to 32 students of the 10th and 11th grades from a Colombian educational institution. Two questionnaires were used for diagnosis and advance of the competences, which were applied one before the pedagogical strategy and one after, respectively. Initially, 16 students formulated the research problem correctly, while, after applying the pedagogical strategy, only one student failed to pose it. It is concluded that the implementation of web 3.0 tools allows students to achieve the necessary competences to develop cross-sectional research projects, taking the educational process both inside and outside the classroom.